Biomechanical analysis of distal stent-graft-induced new entry (SINE) formation in aortic dissection patients / Tan Wei Ting - Tan, Wei Ting (2021)
Distal stent graft-induced new entry (dSINE) is a post-treatment complication with a mortality rate of 26.1-28.6% in patients with aortic dissection (AD). dSINE creates a new path for blood flow, leading to the formation of false lumen, aneurysmal expansion, and aortic rupture. These complications necessitate re-intervention in 30-60% patients. In this study, computational approach was used to investigate potential risk factors for dSINE in aortic dissection patients. Patient-specific simulations were performed based on post thoracic endovascular aortic repair (TEVAR) computed tomography images acquired from six patients (3 dSINE and 3 non-dSINE) to analyse the correlation between anatomical characteristics and stress/strain distribution. Patient geometries were reconstructed for structural simulation. Internal pressure was applied on the inner wall of all models with restrictions of movement at all ends. Hyperelastic material models were applied. Sensitivity analysis was carried out using idealised models to independently assess the effect of stent graft length (50, 80, 100, 130, 160 and 180 mm), stent tortuosity (5˚, 10˚, 20˚ and 30˚) and wedge apposition angle (-25˚, 0˚ and 25˚) at the landing zone on key biomechanical variables. Mismatch in biomechanical properties between the stented and nonstented regions led to high stress at the distal stent graft-vessel interface in all patients, as well as shear strain in the neighboring region, which coincides with the location of tear formation. Increase in von Mises stress was observed with an increase in stent graft tortuosity (from 263 kPa at a tortuosity angle of 50 to 313 kPa at 300). Stress was further amplified by stent graft landing at the inflection point of a curve. Malapposition of the stent graft created an asymmetrical segment within the aorta, thus varying the location and magnitude of the maximum von Mises stress substantially (up to +25.9% with a +25o change in the distal wedge apposition angle). A large increase in stress occurred when the position of the maximum stress fell on the concave surface of the aorta at the distal stent graft-vessel interface. In conclusion, severe dSINE patient has high stent tortuosity with high tortuosity angle at the distal stent-graft landing zone. The mismatch at the stent aortic wall interface induced higher stress with an increase in the tortuosity angle. Stent tortuosity and wedge apposition angle served as important risk predictors for dSINE formation.